اثر الثقافة على الصحة النفسية - فرحان مرعب, ماهر (Sciences de l'Homme et de la Société; Vol. 11 (2014): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ, 2014)
يتناول هذا المقال علاقة الثقافة بالصحة النفسية من خلال الشخصية على اعتبار أن الثقافة هي العامل الأكثر تأثيرًا في تكوين الشخصية لكونها تمثل البيئة التي يجب على الشخصية أن تتوافق معها ومن خلالها، بما تحتوي من قواعد سلوكية وأنماط تنشئة، وعلى أثر هذا التوافق بما يضمه من إشباع أو كبت للحاجات النفسية يتوقف وصفنا لمدى سلامة الصحة النفسية للفرد.   This article discussesthe relationship between culture and psychic health, through the personality, considering the culture more factors impact in the structuring of personality; it represents the environment must adjustment with it and through it, with all the rules of behavior and patterns of socialization, On the basis of this adjustment, With all the satisfaction or suppression of psychological needs, Depends as to how safe the psychic health of the individual